The Portuguese Sample on Social Mobility (1850-1967) - Fonseca, Helder Adegar (2013)
Social Mobility has been an object of a fragmented knoeledge and a theme neglected by the Portuguese historiography, altough it is one of the central issues of the social history in the last tree decades.